The microbiome diversifies long-to short-chain fatty acid-derived N-acyl lipids - Mannochio-Russo, Helena; Charron-Lamoureux, Vincent; van Faassen, Martijn; Lamichhane, Santosh; Nunes, Wilhan D. Goncalves; Deleray, Victoria; Ayala; Adriana; V; Tanaka, Yuichiro; Patan, Abubaker; Vittali, Kyle; et al. (CELL PRESS, 2026)
N-Acyl lipids are important mediators of several biological processes including immune function and stress response. To enhance the detection of N-acyl lipids with untargeted mass spectrometry-based metabolomics, we created a reference spectral library retrieving N-acyl lipid patterns from 2,700 public datasets, identifying 851 N-acyl lipids that were detected 356,542 times. 777 are not documented in lipid structural databases, with 18% of these derived from short-chain fatty acids and found in the digestive tract and other organs. Their levels varied with diet and microbial colonization and in people living with diabetes. We used the library to link microbial N-acyl lipids, including histamine and polyamine conjugates, to HIV status and cognitive impairment. This resource will enhance the annotation of these compounds in future studies to further the understanding of their roles in health and disease and to highlight the value of large-scale untargeted metabolomics data for metabolite discovery.